Distinctive Clinical Profile of Blacks Versus Whites Presenting With Sudden Cardiac Arrest. Issue 5 (4th August 2015) - Reinier, Kyndaron; Nichols, Gregory A.; Huertas-Vazquez, Adriana; Uy-Evanado, Audrey; Teodorescu, Carmen; Stecker, Eric C.; Gunson, Karen; Jui, Jonathan; Chugh, Sumeet S.
Abstract : Background—: Sudden cardiac arrest (SCA) is a major contributor to mortality, but data are limited among nonwhites. Identification of differences in clinical profile based on race may provide opportunities for improved SCA prevention. Methods and Results—: In the ongoing Oregon Sudden Unexpected Death Study (SUDS), individuals experiencing SCA in the Portland, OR, metropolitan area were identified prospectively. Patient demographics, arrest circumstances, and pre-SCA clinical profile were compared by race among cases from 2002 to 2012 (for clinical history, n=126 blacks, n=1262 whites). Incidence rates were calculated for cases from the burden assessment phase (2002–2005; n=1077). Age-adjusted rates were 2-fold higher among black men and women (175 and 90 per 100 000, respectively) compared with white men and women (84 and 40 per 100 000, respectively). Compared with whites, blacks were >6 years younger at the time of SCA and had a higher prearrest prevalence of diabetes mellitus (52% versus 33%; P <0.0001), hypertension (77% versus 65%; P =0.006), and chronic renal insufficiency (34% versus 19%; P <0.0001). There were no racial differences in previously documented coronary artery disease or left ventricular dysfunction, but blacks had more prevalent congestive heart failure (43% versus 34%; P =0.04) and left ventricular hypertrophy (77% versus 58%; P =0.02) and a longer QTc interval (466±36 versus 453±41 milliseconds; P =0.03). Conclusions—: In this US community, the burden of SCA was significantly higher in blacks compared with whites. Blacks with SCA had a higher prearrest prevalence of risk factors beyond established coronary artery disease, providing potential targets for race-specific prevention.